2021
DOI: 10.1038/s41419-020-03353-5
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis-induced muscle atrophy is mediated by elevated levels of circulating TNFα

Abstract: Liver cirrhosis is a critical health problem associated with several complications, including skeletal muscle atrophy, which adversely affects the clinical outcome of patients independent of their liver functions. However, the precise mechanism underlying liver cirrhosis-induced muscle atrophy has not been elucidated. Here we show that serum factor induced by liver fibrosis leads to skeletal muscle atrophy. Using bile duct ligation (BDL) model of liver injury, we induced liver fibrosis in mice and observed sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
2
7
0
Order By: Relevance
“…6). As was also suggested by a previous report 30 , this liver-muscle crosstalk has clinical signi cance because TNF-α is considered as one of the essential factors for skeletal muscle atrophy promoted by hepatic diseases, and this circulating cytokine can be a potential target for the prevention and treatment of NAFLD/NASH-associated skeletal muscle atrophy. Abbreviations ALT, alanine aminotransferase; ANOVA, analysis variance; CDAHFD, choline-de cient, L-amino acidde ned, high-fat diet; CE-TOFMS, capillary electrophoresis time-of-ight mass spectrometry; CE-QqQMS, capillary electrophoresis-triple quadrupole mass spectrometry; FoxO, forkhead box-containing protein; HCA, hierarchical cluster analysis; HE, hematoxylin and eosin; IGF, insulin-like growth factor; NAFLD, nonalcoholic fatty liver disease; NAS, non-alcoholic fatty liver disease activity score; NASH, non-alcoholic steatohepatitis; PCA, principal component analysis; qRT-PCR, quantitative transcription PCR; SAM, senescence-accelerated mouse; SAMP, senescence-accelerated mouse prone; SAMR, senescenceaccelerated mouse resistant; TNF, tumour necrosis factor; 8-OHdG, 8-hydroxy-2'-deoxyguanosine Declarations Figures…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…6). As was also suggested by a previous report 30 , this liver-muscle crosstalk has clinical signi cance because TNF-α is considered as one of the essential factors for skeletal muscle atrophy promoted by hepatic diseases, and this circulating cytokine can be a potential target for the prevention and treatment of NAFLD/NASH-associated skeletal muscle atrophy. Abbreviations ALT, alanine aminotransferase; ANOVA, analysis variance; CDAHFD, choline-de cient, L-amino acidde ned, high-fat diet; CE-TOFMS, capillary electrophoresis time-of-ight mass spectrometry; CE-QqQMS, capillary electrophoresis-triple quadrupole mass spectrometry; FoxO, forkhead box-containing protein; HCA, hierarchical cluster analysis; HE, hematoxylin and eosin; IGF, insulin-like growth factor; NAFLD, nonalcoholic fatty liver disease; NAS, non-alcoholic fatty liver disease activity score; NASH, non-alcoholic steatohepatitis; PCA, principal component analysis; qRT-PCR, quantitative transcription PCR; SAM, senescence-accelerated mouse; SAMP, senescence-accelerated mouse prone; SAMR, senescenceaccelerated mouse resistant; TNF, tumour necrosis factor; 8-OHdG, 8-hydroxy-2'-deoxyguanosine Declarations Figures…”
Section: Discussionmentioning
confidence: 55%
“…The role of TNF‐α in skeletal muscle atrophy has been extensively investigated 27–32 . One study demonstrated that TNF‐α produced in fibrotic liver was transported to muscle through the bloodstream, leading to atrophy of skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…6). As was also suggested by a previous report 30 , this liver-muscle crosstalk has clinical signi cance because TNF-α is considered as one of the essential factors for skeletal muscle atrophy promoted by hepatic diseases, and this circulating cytokine can be a potential target for the prevention and treatment of NAFLD/NASH-associated skeletal muscle atrophy. Abbreviations ALT, alanine aminotransferase; ANOVA, analysis variance; CDAHFD, choline-de cient, L-amino acidde ned, high-fat diet; CE-TOFMS, capillary electrophoresis time-of-ight mass spectrometry; CE-QqQMS, capillary electrophoresis-triple quadrupole mass spectrometry; FoxO, forkhead box-containing protein; HCA, hierarchical cluster analysis; HE, hematoxylin and eosin; IGF, insulin-like growth factor; NAFLD, nonalcoholic fatty liver disease; NAS, non-alcoholic fatty liver disease activity score; NASH, non-alcoholic steatohepatitis; PCA, principal component analysis; qRT-PCR, quantitative transcription PCR; SAM, senescence-accelerated mouse; SAMP, senescence-accelerated mouse prone; SAMR, senescenceaccelerated mouse resistant; TNF, tumour necrosis factor; 8-OHdG, 8-hydroxy-2'-deoxyguanosine…”
Section: Discussionmentioning
confidence: 55%
“…Patients with chronic liver disease have reduced muscle mass 48 . Kurosawa et al used the bile duct ligation model of liver injury to demonstrate a causal relationship between liver fibrosis and muscle wasting 49 , highlighting the importance of liver function in systemic metabolism. Defective lipid metabolism in the liver is becoming accepted as a contributor to peripheral tissue wasting in cancer cachexia 18 , underlining the importance of lipid metabolism in the pathology of cachexia.…”
Section: Discussionmentioning
confidence: 99%